Dynamic Modeling and CAE Cosimulation Method for Heavy-Duty Concrete Spreader - Shiying Zhang; Ke Zhang; Bo Song; Wenda Yu; Dong Li (Advances in Civil Engineering)
This paper presents the dynamic model of heavy-duty concrete spreader with liquid-solid rigid-flexible coupling by means of mathematical modeling and CAE cosimulation. The mathematical method of liquid-solid dynamic model of heavy-duty concrete spreader is described. Based on the liquid-solid coupling system, two degrees of freedom are added to change the model into a liquid-solid rigid-flexible coupling model, and the calculation process of the model is given in detail. The results show that, considering two flexible body factors, the solution scale is relatively large and the complexity of mathematical model derivation is increased. It is very difficult to establish a general dynamic equation which can be easily solved by computer. Therefore, this paper presents a new method of CAE cosimulation of liquid-solid rigid-flexible coupling. This method is divided into two parts: the computer simulation process of liquid-solid coupling and the computer simulation process of rigid-flexible coupling. First, the fluid-solid coupling is carried out by COMSOL software, and then the rigid-flexible coupling is carried out by HyperMesh software, Ansys software, and Adams software. This method can easily establish the dynamic model of the liquid-solid rigid-flexible coupling system, which provides a new idea for the simulation of heavy-duty concrete spreader. The simulation results can provide valuable insights into product design and structural optimization.